Multiplex Nucleic Acid Amplification Test for Diagnosis of Dengue Fever, Malaria, and Leptospirosis - Waggoner, Jesse J. (American Society for Microbiology, 2014)
Dengue, leptospirosis, and malaria are among the most common etiologies of systemic undifferentiated febrile illness (UFI) among travelers to the developing world, and these pathogens all have the potential to cause life-threatening illness in returned travelers. The current study describes the development of an internally controlled multiplex nucleic acid amplification test for the detection of dengue virus (DENV) and Leptospira and Plasmodium species, with a specific callout for Plasmodium falciparum (referred to as the UFI assay). During analytical evaluation, the UFI assay displayed a wide dynamic range and a sensitive limit of detection for each target, including all four DENV serotypes. In a clinical evaluation including 210 previously tested samples, the sensitivities of the UFI assay were 98% for DENV (58/59 samples detected) and 100% for Leptospira and malaria (65/65 and 20/20 samples, respectively). Malaria samples included all five Plasmodium species known to cause human disease. The specificity of the UFI assay was 100% when evaluated with a panel of 66 negative clinical samples. Furthermore, no amplification was observed when extracted nucleic acids from related pathogens were tested. Compared with whole-blood samples, the UFI assay remained positive for Plasmodium in 11 plasma samples from patients with malaria (parasitemia levels of 0.0037 to 3.4%). The syndrome-based design of the UFI assay, combined with the sensitivities of the component tests, represents a significant improvement over the individual diagnostic tests available for these pathogens.